2018
DOI: 10.21037/jtd.2018.02.19
|View full text |Cite
|
Sign up to set email alerts
|

Transcatheter closure of atrial septal defect: principles and available devices

Abstract: There has been a remarkable improvement in the treatment strategy of secundum atrial septal defect (ASD) over the last few decades. Indebted to the improvement in device technology and procedural techniques, transcatheter closure of ASD is currently accepted as the treatment of choice in most patients with secundum ASD. Recent generation devices enable easy and safe deployment of device with the properties of adequate flexibility, re-capturability and repositioning. Use of biocompatible materials with improved… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 53 publications
0
37
1
Order By: Relevance
“…No erosion or perforation event was noted 3). Because of these advantages, the GSO device was expected to perform well in smaller defects especially with deficient retro-aortic rims, those in small children, or multi-fenestrated defects, when covering most of the atrial septum is necessary 11). In our study, although there were few patients in GSO group (n=17), the small children under 15 kg were highest (29.4%) in that group, and there was also no significant difference of defect size to BSA ratio among the 3 groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…No erosion or perforation event was noted 3). Because of these advantages, the GSO device was expected to perform well in smaller defects especially with deficient retro-aortic rims, those in small children, or multi-fenestrated defects, when covering most of the atrial septum is necessary 11). In our study, although there were few patients in GSO group (n=17), the small children under 15 kg were highest (29.4%) in that group, and there was also no significant difference of defect size to BSA ratio among the 3 groups.…”
Section: Discussionmentioning
confidence: 99%
“…In general, a sufficient septal rim should surround an ASD >5 mm in all directions. Although rim deficiency may potentially increase the risk of complications such as device embolization, erosion and encroachment of device onto nearby cardiac structures, most ASDs with deficient rims were closed successfully and included in this study 11)12). The exclusion criteria were as follows: any associated complex congenital heart disease or other types of ASDs (e.g., sinus venosus and ostium primum defects), bleeding disorders, and any contraindication to antiplatelet therapy, active systemic infection, and intracardiac thrombus.…”
Section: Methodsmentioning
confidence: 99%
“…The differences in For a multifenestrated large aneurismatic septum, a non-self -centering device placement may be a good option. 62 Sometimes in such cases, in order to close all the defects while stabilizing the floppy septum, one may consider puncturing the central part of the septum with a transseptic needle and implanting through this hole a non-self -centering implant.…”
Section: Short Review Of the Devices Available Inmentioning
confidence: 99%
“…One recent case series reported that absence of the aortic rim was common finding among patients who developed erosion [126] . Subsequently, other putative risk factors were also reported as physicians modified their practices and over sizing became less common [127] . Specifically, deficient aortic or SVC rim size, along with balloon sizing were associated with increased risk of erosion [128] .…”
Section: Cardiac Erosion After Percutaneous Asd Interventionmentioning
confidence: 99%